Breast Capsular Cerebrospinal Fluid Collection from Migration of a Ventriculoperitoneal Shunt Catheter. Issue 3 (March 2016) - Knaus, William J.; Kamali, Parisa; Chun, Yoon; Lin, Samuel J.
Abstract : Summary: In this case report we have described an unusual complication of ventriculoperitoneal shunt migration into a breast implant capsule. The patient was appropriately diagnosed with computed tomographic imaging and successfully managed with shunt revision and cerebrospinal fluid aspiration. Given the high complication profile of ventriculoperitoneal shunt catheters, this case suggests an opportunity for improved perioperative communication between plastic surgeons and neurosurgeons in patients with breast implants. Coordination regarding the subcutaneous catheter tunneling may hopefully minimize the risk of this complication.